Translatome Analyses Using Conditional Ribosomal Tagging in GABAergic Interneurons and Other Sparse Cell Types. Issue 1 (5th March 2020) - Mahadevan, Vivek; Peltekian, Areg; McBain, Chris J.
Abstract: GABAergic interneurons comprise a small but diverse subset of neurons in the mammalian brain that tightly regulate neuronal circuit maturation and information flow and, ultimately, behavior. Because of their centrality in the etiology of numerous neurological disorders, examining the molecular architecture of these neurons under different physiological scenarios has piqued the interest of the broader neuroscience community. The last few years have seen an explosion in next‐generation sequencing (NGS) approaches aimed at identifying genetic and state‐dependent subtypes in neuronal diversity. Although several approaches are employed to address neuronal molecular diversity, ribosomal tagging has emerged at the forefront of identifying the translatomes of neuronal subtypes. This approach primarily relies on Cre recombinase–driven expression of hemagglutinin A (HA)–tagged RiboTag mice exclusively in the neuronal subtype of interest. This allows the immunoprecipitation of cell‐type‐specific, ribosome‐engaged mRNA, expressed both in the soma and the neuronal processes, for targeted quantitative real‐time PCR (qRT‐PCR) or high‐throughput RNA sequencing analyses. Here we detail the typical technical caveats associated with successful application of the RiboTag technique for analyzing GABAergic interneurons, and in theory other sparse cell types, in the central nervous system. Published 2020. U.S. Government. Basic Protocol 1 : Breeding mice to obtain RiboTag homozygosity Support Protocol 1 : Detection of ectopic Cre recombinase expression Basic Protocol 2 : The RiboTag assay Support Protocol 2 : Real‐time quantitative PCR (qRT‐PCR) assay of RiboTag‐derived cell‐type‐specific RNA Support Protocol 3 : Construction of cell‐type‐specific RNA‐seq library Support Protocol 4 : Secondary analyses of RiboTag‐derived RNA‐seq dataset